2020
DOI: 10.1001/jama.2020.16641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Praliciguat on Peak Rate of Oxygen Consumption in Patients With Heart Failure With Preserved Ejection Fraction

Abstract: with preserved ejection fraction (HFpEF) is often characterized by nitric oxide deficiency.OBJECTIVE To evaluate the efficacy and adverse effects of praliciguat, an oral soluble guanylate cyclase stimulator, in patients with HFpEF.DESIGN, SETTING, AND PARTICIPANTS CAPACITY HFpEF was a randomized, double-blind, placebo-controlled, phase 2 trial. Fifty-nine sites enrolled 196 patients with heart failure and an ejection fraction of at least 40%, impaired peak rate of oxygen consumption (peak V O 2 ), and at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 32 publications
0
56
3
1
Order By: Relevance
“…More optimal blood flow redistribution may represent an improvement in the heterogeneity of skeletal myofiber–perfusion matching, as previously demonstrated for nitrite therapy, 34,35 and this too may partially explain the improvement in O 2 kinetics and Dm during acute exercise with nitrite. Despite the evidence for impaired NO–cGMP signalling in HFpEF, clinical trials evaluating the nitrate–NO–cGMP axis in patients with HFpEF have failed to improve exercise capacity and quality of life, including organic nitrates, 36 soluble guanylate cyclase stimulators, 37–39 and phosphodiesterase inhibitors 40,41 . A key distinguishing feature of inorganic nitrite is the fact that haemodynamic and peripheral improvements at rest are less than what is observed with exercise.…”
Section: Discussionmentioning
confidence: 99%
“…More optimal blood flow redistribution may represent an improvement in the heterogeneity of skeletal myofiber–perfusion matching, as previously demonstrated for nitrite therapy, 34,35 and this too may partially explain the improvement in O 2 kinetics and Dm during acute exercise with nitrite. Despite the evidence for impaired NO–cGMP signalling in HFpEF, clinical trials evaluating the nitrate–NO–cGMP axis in patients with HFpEF have failed to improve exercise capacity and quality of life, including organic nitrates, 36 soluble guanylate cyclase stimulators, 37–39 and phosphodiesterase inhibitors 40,41 . A key distinguishing feature of inorganic nitrite is the fact that haemodynamic and peripheral improvements at rest are less than what is observed with exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from the VITALITY-HFpEF randomized placebo-controlled trial showed that 24-week treatment with Vericiguat compared with placebo did not improve the physical limitation score (67). Similarly, Praliciguat did not improve significantly the Peak Rate of Oxygen Consumption, thus not supporting its use in patients with HFpEF (CAPACITY HFpEF trial) (68).…”
Section: Treatment Of Hfpef: Knowledge Gaps and Future Perspectivesmentioning
confidence: 99%
“…Finally, as randomized trials in nephrology with hard endpoints (i.e., death or cardiovascular events) are difficult to perform and scarce, several studies, including elegant randomized research efforts in patients with CKD include intermediate cardiac end points, such as left-ventricular mass index and left-ventricular ejection fraction [76, 77]. As of this writing, trials in other patient populations (i.e., individuals with heart failure) have used CPET parameters as intermediate cardiovascular endpoints [78, 79]. On this basis, using comprehensive CPET end points could be a valid option also for cardiorenal outcome trials [69]; for this to happen, long-term and optimally designed studies should first evaluate the association of key CPET parameters, such as VO 2 peak, with key outcomes such as cardiovascular and all-cause mortality specifically in patients with CKD.…”
Section: Potential Clinical Applications Of Cpet In Patients With Ckdmentioning
confidence: 99%